Ecocriticism: Basic Concerns - Muhammad Irfan Haider (بازیافت)
The main concern of Ecocriticism is to explore the relationship between literature and the physical environment. It analyzes the nature of expressions made in literary texts about nature and external environment. At its core, it is a reflexive study of literary texts, which foster anthropocentric power-based narratives. This paper describes the philosophical, ethical and political epistemology of Ecocriticism. In the Philosophical section, the arguments of Spinoza and Bacon are used, while in the Ethical section, the philosophies of Erne Naees are elaborated. In the political context, two sub-schools of Ecocriticism have been interpreted, Ecofeminism and postcolonial environmentalism. This is intended to show that the spread of Ecocriticism discussions in various academic and intellectual dimensions is not only an affirmation of its multidisciplinary approach. But also an argument for Ecocriticism to be a stable field of knowledge and literary Criticism.